Cadmium, does its presence warn us of anthropogenic pollution? - Gamboa, Nadia (2019)
Cadmium is very scarce in nature and its presence in the environment is due to industrial development. Irresponsible waste management makes it appear in freshwaters and agricultural soils. It is very toxic and bioaccumulative, causing itai-itai disease.